Hybrid dizziness counseling with vestibular rehabilitation in participants with chronic dizziness: a comparison of dizziness handicap - Chua, Kenneth Wei De; Deng, Jing; Yuen, Heng Wai (Frontiers in Audiology and Otology, 2023)
Introduction Patients with chronic dizziness often have an unremarkable laboratory vestibular examination and have medical clearance from other specialties. However, functional impairments are still significant and affect patients' quality of life. Recent diagnostic criteria and identification of persistent postural perceptual dizziness (PPPD) have helped us to better understand the psychological-somatic manifestations of organic disorders. As the literature suggests good efficacy using a combination of cognitive behavior therapy (CBT) and vestibular rehabilitation, we compared the efficacy of a hybrid protocol using dizziness handicap inventory (DHI) as an outcome measure amongst the different sub-types of chronic dizziness. Methods This was an observational study with 35 participants allocated to three different groups: those who strictly fulfilled the PPPD criteria, those with spontaneous episodic vestibular syndrome, and participants with non-specific dizziness. We compared the DHI total and sub-domain scores at baseline and 6 months post-intervention for differences. All participants undertook three sessions in 6 months. Results The total DHI scores were reduced in all three groups. However, the DHI total on average was 11 points higher in the episodic vestibular syndrome group. The emotional sub-domain scores were also reduced in all three groups, but the functional and physical scores were significantly higher in the episodic vestibular group. Conclusion A hybrid protocol worked best for typical PPPD patients who strictly fulfilled the criteria followed by participants in the non-specific dizziness group. When symptoms were episodic in spontaneous vestibular syndrome, only emotional handicap was reduced at 6 months, but functional and physical handicap scores remained high. Regardless, the DHI total scores in all groups were significantly reduced, possibly due to CBT reducing the anxiety that results from a lack of understanding of the clinical diagnoses.